Gender identity disorder: role of the gynecologist - Kondapalli, Saraswathi; Gopalan, Ushadevi; Karthika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Gender dysphoria refers to distress that is caused by a sense of incongruity between an individual's self-identified gender and natal sex. Over 1.4 million adults are identified as transgender. Transpatients face many barriers when it comes to basic health needs including education, housing, and health care. Because of these barriers, many patients do not receive proper health care that they need. Additionally, because of certain high-risk behaviours as well as long-term hormonal therapy, transpatients have different routine health care needs that should be addressed in the primary care setting. Diagnosis is made in accordance with the diagnostic and statistical manual of mental disorders and treatment first involves psychiatric therapy, which can help determine a patient's true goals in regards to achieving gender identity. Patients who wish to undergo transition to the opposite sex must undergo a supervised real-life test and often are treated with hormonal therapy to develop physical characteristics consistent with their gender identity. Many of these individuals have undergone, or plan to undergo, gender-affirming surgery. While not all gender-affirming surgeries are provided by obstetricians and gynecologists (OBGYNs). It is a multi-disciplinary team which involves psychiatrist, endocrinologist, gynecologist and plastic surgeon. OBGYNs are uniquely skilled to perform certain gender-affirming surgeries such as hysterectomies, bilateral oophorectomies. In this case report we discuss the medical and surgical options available for the transgender population. In addition, it also highlights the role of gynecologists in having care for this population, and should be knowledgeable about the general principles of transgender health.